2019
DOI: 10.3324/haematol.2018.198838
|View full text |Cite
|
Sign up to set email alerts
|

The promise of CD4+FoxP3+ regulatory T-cell manipulation in vivo: applications for allogeneic hematopoietic stem cell transplantation

Abstract: CD4 + FoxP3 + regulatory T cells (Tregs) are a non-redundant population critical for the maintenance of self-tolerance. Over the past decade, the use of these cells for therapeutic purposes in transplantation and autoimmune disease has emerged based on their capacity to inhibit immune activation. Basic science discoveries have led to identifying key receptors on Tregs that can regulate their proliferation and function. Notably, the understanding that IL-2 signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 196 publications
(220 reference statements)
1
14
0
Order By: Relevance
“…[21][22][23][24][25] These associations with aGVHD have not been studied in the setting of TCD or haploidentical HCT, where the mechanisms governing expansion of alloreactive T cells and recovery of Tregs may differ. 26 There is a poor understanding of aGVHD development after TCD transplantation, [27][28][29][30] but expansion of both polyclonal and oligoclonal alloreactive T cells has been demonstrated. Although CD4 1 IR did not seem to protect against aGVHD itself in our cohorts, it may translate to lower mortality after severe aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] These associations with aGVHD have not been studied in the setting of TCD or haploidentical HCT, where the mechanisms governing expansion of alloreactive T cells and recovery of Tregs may differ. 26 There is a poor understanding of aGVHD development after TCD transplantation, [27][28][29][30] but expansion of both polyclonal and oligoclonal alloreactive T cells has been demonstrated. Although CD4 1 IR did not seem to protect against aGVHD itself in our cohorts, it may translate to lower mortality after severe aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells play an important role in the resistance to immune rejection in kidney transplantation. Treg cells can speci cally inhibit autoreactive T cells and are important cells involved in peripheral immune tolerance [29]. It has been reported that injection of MSCs can improve kidney transplant rejection and induce immune tolerance by increasing the proportion of Treg cells [5,30].…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies to induce tolerance were the subject of a CIRM Workshop and Perspective in 2015, and are discussed further there . A third general approach to address complications of tissue mismatch involves development of targeted therapies for the treatment of chronic GVHD including the in vivo expansion of endogenous regulatory T lymphocytes (Treg) with low‐dose interleukin‐2 or ex vivo expansion of Treg subsets followed by their in vivo administration …”
Section: Medical and Procedural Risks Of Hsctmentioning
confidence: 99%
“…44 with low-dose interleukin-2 or ex vivo expansion of Treg subsets followed by their in vivo administration. 47…”
Section: Tissue Mismatchmentioning
confidence: 99%